Rapamycin for longevity: the pros, the cons, and future perspectives - Roark, Kelley M.; Iffland, Philip H. (Frontiers in Aging, 2025)
Rapamycin, an antibiotic discovered in the 1970s from Streptomyces hygroscopicus on Easter Island (Rapanui), has become a critical tool in biomedical research. Initially recognized for its potent antifungal and immunosuppressive properties, rapamycin has recently gained significant attention for anti-aging therapy and seizure treatment via mTOR pathway inhibition. The mechanistic target of the rapamycin (mTOR) pathway is an evolutionarily conserved metabolic signaling cascade that regulates cell division, growth, and survival. There is growing evidence that mTOR pathway activity accelerates aging and the development of age-related diseases including cancer, atherosclerosis, diabetes, and declining immune function. Therefore physicians and “biohackers” are using mTOR inhibition via rapamycin (and rapamycin analogs) off-label for prevention of age-related conditions despite not being widely recognized as a treatment by the broader clinical community. Currently, rapamycin (i.e., sirolimus and everolimus) is FDA approved for the prevention of transplant organ rejection and for anti-seizure therapy in Tuberous Sclerosis Complex (TSC; caused by variants in TSC1 or 2). We aim to summarize the mTOR pathway, the impact rapamycin has on the mTOR pathway, and the state of rapamycin use in the field of aging and longevity. Importantly, we will discuss the gaps in knowledge, pitfalls, and potential for the use of rapamycin to prevent aging/age-related disease and discuss the lessons learned from achieving FDA approval of evirolimus for TSC-related seizures after many years of off-label use.